Puerto Rican Chicago : Schooling the City, 1940-1977 - Velázquez, Mirelsie, 1975- (Book collections on Project MUSE., 2022)
"The postwar migration of Puerto Rican men and women to Chicago brought thousands of their children into city schools. These children's classroom experience continued the colonial project begun in their homeland, where American ideologies had dominated Puerto Rican education since the island became a US territory. Mirelsie Velázquez tells how Chicago's Puerto Ricans pursued their educational needs in a society that constantly reminded them of their status as second-class citizens. Communities organized a media culture that addressed their concerns while creating and affirming Puerto Rican identities. Education also offered women the only venue to exercise power, and they parlayed their positions to take lead roles in activist and political circles. In time, a politicized Puerto Rican community gave voice to a previously silenced group--and highlighted that colonialism does not end when immigrants live among their colonizers. A perceptive look at big-city community building, Puerto Rican Chicago reveals the links between justice in education and a people's claim to space in their new home"--